Differentiating between stopover and staging sites: functions of the southern and northern Yellow Sea for long‐distance migratory shorebirds. (3rd September 2013) - Ma, Zhijun; Hua, Ning; Peng, Hebo; Choi, Chiyeung; Battley, Phil F.; Zhou, Qianyan; Chen, Ying; Ma, Qiang; Jia, Na; Xue, Wenjie; Bai, Qingquan; Wu, Wei; et al.
Abstract : Evidence‐based protection of migratory birds at flyway levels requires a solid understanding of their use of 'stopping sites' during migration. To characterize the site use of northward‐migration great knots Calidris tenuirostris in China, we compared length of stay and fuel deposition during northward migration at areas in the south and the north of the Yellow Sea, a region critical for migrating shorebirds. Radio‐tracking showed that at the southern site great knots stayed for only short periods (2.3 ± 1.9 d, n = 40), and bird captures showed that they did not increase their mean body mass while there. In the north birds stayed for 1 month (31.0 ± 13.6 d, n = 22) and almost doubled their mean body mass. Fuel consumption models suggest that great knots departing from the northern Yellow Sea should be able to fly nonstop to the breeding grounds, whereas those from the south would require a refueling stop further north. These results indicate that the study sites in the northern and southern Yellow Sea serve different roles: the southern site acts as a temporary stopover area that enables birds with low fuel stores to make it to main staging areas further north, while the northern site serves as the critical staging site where birds refuel for the next leg of their migration. The rapid turnover rate in the southern Yellow Sea indicates that many more birds use that area than are indicated by peak counts. Differential use of the southern and northern sites indicates that both play crucial roles in the ability of great knots to migrate successfully.